Organisational distance between GCC Islamic banks and their subsidiaries in Malaysia: a knowledge transfer perspective - Elmabrok, Ali Abusalah; Ng, Kim-Soon; M. Ago, Fathi Khalifa (AJAST, 2018)
GCC Islamic banks‟ subsidiaries in Malaysia have seen the going through tough, strapped by paltry returns and stymied by fierce competition from the local banks. The future of these GCC Islamic bank subsidiaries in Malaysia is being scrutiny through by when their headquarters back home is reaping a much higher return on equity. Thus, this research paper is conducted to investigate the organisational distance between the headquarters of GCC Islamic banks and their subsidiaries in Malaysia. Five large GCC Islamic banks subsidiaries in Malaysia were identified to document the organisational distance between headquarters of these banks and their subsidiaries in Malaysia. The data of this study were collected through sending out questionnaires to subsidiaries of GCC Islamic banks in Malaysia, as well as conducting semi-structured interviews with the top managements of these banks and through reviewing, tracking and comparing the information of their past and current from literature works to report the impact of organisational distance on knowledge transfer. The results show that the GCC Islamic banks subsidiaries in Malaysia are at the moderate level of organisational distance on knowledge transfer. The four factors which are structures, routines, decision-making and organizational culture, significantly influence the organisational distance between subsidiaries and the headquarters. The findings result in developing a conceptual unifying model of knowledge transfer between Islamic banking and financial services within Islamic banks and provide impetus for future empirical testing.